Double blind clinical trial on a lactose-free and a lactose-containing formula in the treatment of acute diarrhea in children - Sri Lestari; Agus Firmansyah; Zakiudin Munasir (Paediatrica Indonesiana, 2006)
Background Lactose intolerance is a common complication ofdiarrhea in young children particularly that due to rotaviral infec-tion. A meta-analysis study evaluated the use of undiluted lactosecontaining formula or cow’s milk during an episode of diarrhea. Itwas concluded that routine dilution of milk and the use of lactose-free milk formula are not necessary.Objective To evaluate the effect of lactose free formula comparedwith lactose-containing milk formula during acute diarrheal episodein outpatient setting.Methods A total of 56 children with acute diarrhea with mild-mod-erate or no dehydration attending to the outpatient clinic were ran-domly assigned to receive a lactose-free formula (Nestle Nan ® freelactose) or lactose-containing milk formula (Nestle Nan 2 ® formula)after initial rehydration. Comparisons of stool frequency, durationof diarrhea and treatment failure rates were noted. Treatment fail-ure was defined as clinical requirement for intravenous infusionafter rehydration or prolonged diarrhea (>7 days).Results The duration of diarrhea was similar between the twogroups (P=0.195) in spite of two children who received lactosefree formula did not resolve from diarrhea within 7 days of treat-ment. The median of stool frequency was indifferent in the twogroups (P=0.199) in rotavirus gastroenteritis; there were no differ-ences in the duration of diarrhea or the stool frequency.Conclusion Children without dehydration or with mild dehydra-tion tolerated to lactose-containing formula as well as lactose-freeformula for the treatment of acute diarrhea